Influence of aggregate interference on the crack propagation of asphalt concrete by the configurational force fracture criterion. (30th December 2020) - Du, Jianhuan; Ai, Changfa; An, Shaoke; Ren, Dongya; Qiu, Yanjun
Highlights: The configurational force fracture criterion excludes the drawbacks of the traditional fracture mechanics criterion. The crack propagation path can be extracted by the PHILSM Field Variables. The influence mechanism of aggregate on crack propagation can be revealed trough the change of crack tip configuration. Abstract: In this study, the influence of aggregate interference on the crack propagation of asphalt concrete by the configurational force fracture criterion has been investigated. Since the presence of aggregates inside the asphalt concrete generally changes the nearby stress distribution and exerts a significant impact on the behavior of composite crack growth, the crack passing through single aggregate and asymmetric double aggregate are simulated based on the configurational force fracture criterion using the extended finite element method (XFEM). It was observed that under pure tensile load, the crack will propagate away from the aggregate; but when the crack has an initial deflection angle β, the crack will propagate towards the aggregate, until the crack "pierces" the second aggregate. In terms of the crack tip configurational force, the aggregate has an interference effect on the crack propagation, where the crack tip configurational force decreases with an increase in the aggregate particle size. Moreover, the interference of aggregate on the crack propagation path has a certain limit. It was also found that under the interference of asymmetric double-aggregate; larger the particle size range of the aggregate, easier is the formation of overhead structure inside the material, which eventually results in local instability. This instability drastically affects the crack resistance of the asphalt mixture.